Ecotoxicological analysis during the removal of carbofuran in fungal bioaugmented matrices - Ruiz Hidalgo, Karla María (2016)
Biomixtures are used for the removal of pesticides from agricultural wastewater. As biomixtures employ high content of lignocellulosic substrates, their bioaugmentation with ligninolytic fungi represents a novel approach for their enhancement. Nonetheless, the decrease in the concentration of the pesticide may result in sublethal concentrations that still affect ecosystems. Two matrices, a microcosm of rice husk (lignocellulosic substrate) bioaugmented with the fungus Trametes versicolor and a biomixture that contained fungally colonized rice husk were used in the degradation of the insecticide/nematicide carbofuran (CFN). Elutriates simulating lixiviates from these matrices were used to assay the ecotoxicological effects at sublethal level over Daphnia magna (Straus) and the fish Oreochromis aureus (Steindachner) and Oncorhynchus mykiss (Walbaum). Elutriates obtained after 30 d of treatment in the rice husk microcosms at dilutions over 2.5% increased the offspring of D. magna as a trade-off stress response, and produced mortality of neonates at dilutions over 5%. Elutriates (dilution 1:200) obtained during a 30 d period did not produce alterations on the oxygen consumption and ammonium excretion of O. mykiss, however these physiological parameters were affected in O. aureus at every time point of treatment, irrespective of the decrease in CFN concentration. When the fungally colonized rice husk was used to prepare a biomixture, where more accelerated degradation is expected, similar alterations on the responses by O. aureus were achieved. Results suggest that despite the good removal of the pesticide, it is necessary to optimize biomixtures to minimize their residual toxicity and potential chronic effects on aquatic life.